Introduction to public health - Schneider, Mary-Jane; Schneider, Henry S. (Jones & Bartlett Learning, 2017)
Up to date coverage of the newest developments in infectious disease, injury control, environmental health controversies, the reform of the American healthcare system, and more Vivid presentation of Public Health principles through current stories in the news, such as Ebola in the United States, e cigarettes, eating disorders, the California Measles outbreak, and traumatic brain injury in the NFL.